Shallow Versus Deep Uncertainties in Natural Hazard Assessments. (2nd April 2013) - Stein, Seth; Stein, Jerome L.
Abstract : In Shakespeare's Henry IV, Glendower says, "I can call spirits from the vasty deep, " and Hotspur replies, "Why, so can I, or so can any man; but will they come when you do call for them?"